KADAR 1-DEOXYNOJIRIMYCIN DAN AKTIFITAS PENGHAMBATAN TERHADAP ENZIM Α-GLUKOSIDASE DALAM EKSTRAK, TEPUNG EKSTRAK DAN TEPUNG INSTANT DAUN MURBAI (Morus alba L) [1-Deoxynojirimycin Content and Inhibitory Activity on Α-Glucosidase Enzyme of Extract, Extract Po - Kesuma Sayuti; Norio Muto (Jurnal Teknologi dan Industri Pangan, 2010)
Many researcher had proved that the mulberry leaves had effective enzyme inhibitory activity. For easy serving, the leaves had been processed as extract powder and instant powder. In this study, The 1-deoxynojirimycin (DNJ) content, was analyzed by high-performance liquid chromatography. Additionally, the inhibitory activity of extract, extract powder and mulberry (Morus alba L) instant powder was studied by using rat intestinal homogenate enzyme, that was measured using maltose, and the absorbance was determined at 505 nm. Slightly higher than that in. The results showed that DNJ content in mulberry water fraction was 166.48 mg/g ± 3.24, in the extract powder was (0.82mg/g ± 0.01) which was the instant powder (0.75 mg/g ±0.01). The extract, extract powder and the mulberry instant powder had effective enzyme inhibitory activity. Inhibitory activity on the enzyme by extract was stronger than the extract powder, and inhibitory activity on the enzyme by extract powder was stronger than the instant powder.